The Main Nile Valley at the End of the Pleistocene (28–15 ka): Dispersal Corridor or Environmental Refugium? - Leplongeon, Alice (Frontiers in Earth Science, 2021)
Under the present environmental conditions, the Nile Valley acts as a ‘natural’ route between Africa and Eurasia, and is often considered as a corridor of dispersals out of and back into Africa in the past. This review aims to address the role played by the Nile Valley at the end of the Pleistocene (28-15ka) in the context of post-out of Africa modern human dispersals. Genetic studies based on both modern and ancient DNA suggest pre-Holocene dispersals ‘back into Africa’ as well as genetic interactions between modern humans across Africa and the Levant. During the Last Glacial, the lowering, or even desiccation of major eastern African lakes, including Lake Victoria, reduced the White Nile to a highly seasonal river, depriving the main Nile from its most important tributary in the dry season. This had deep consequences, the modalities of which are still debated, on the behaviour of the main Nile and the landscape around the Nile Delta. Despite this shift to more arid conditions, there is abundant evidence for human occupation in the main Nile Valley. Combining available geological, palaeoenvironmental, anthropological, genetic and archaeological data, we discuss problems encountered when trying to reconcile results from different fields, current limitations of the available data and research perspectives to further address the role of the Nile Valley as a corridor of dispersal or environmental refugium at the end of the Pleistocene.